PERBANDINGAN PERTAMBAHAN PANJANG BADAN BAYI USIA 6-12 BULAN YANG DIBERI BUBUR BAYI SEHAT (Studi Cohort pada Bayi Usia 6-12 Bulan di Kelurahan Kalongan, Kecamatan Purwodadi, Kabupaten Grobogan) - Baitunnisa Nurul Af-idah; Sri Priyantini Mulyani (Jurnal Riset Multidisiplin Edukasi, 2026)
Complementary foods (MPASI) play a crucial role in supporting infant growth. Healthy baby porridge sold on the street is a practical and economical choice, but its exact nutritional content is unknown. This study aimed to determine the difference in average height between infants fed healthy baby porridge sold on the street and those not. The study used a cohort design with 54 infants aged 6-12 months in Kalongan Village, Purwodadi District, Grobogan. Bivariate data analysis used the Mann-Whitney U test. The results showed that infants fed healthy baby porridge sold on the street had an average height gain of 1.03 ± 0.76 cm, while those not fed healthy baby porridge had an average height gain of 1.13 ± 0.59 cm.